Optimalisasi Hasil Belajar Siswa Kelas Viii Dalam Pendidikan Agama Islam Dan Budi Pekerti Melalui Metode Seminar Kelas Semester Gasal Tahun Pelajaran 2015/2016(Studi Kasus Di Smp N 1 Surakarta) - Wulan, Natalia Arum, Dra. Mahasri Shobahiya, M.Ag (2016)
Islamic Education Learning and ethic kindness at 1 Public Junior High School of Surakarta have applied the model of active learning but model deliver a lecture remain to be pledge in study process. Result learns to pass talk speech method not yet last for giving optimal contribution. From these background so emerge of problem statements that was what study method of class seminar active learning can optimalized of students learning result VIII class of 1 Public Junior High School of Surakarta? This research purpose to identify the VIII class students learning result optimalized of at Islamic Education Learning and ethic kindness through method of class seminar odd semester 2015/2016 school year at 1 Public Junior High School of Surakarta. the subject was used in this research was VIII class students of 1 Public Junior High School of Surakarta odd semester 2015/2016 school year with sistematic sampling technique. Amount of accurate was 89 students, consisted of 38 men students and 51 woman studenst. While its object was students learn result of VIII class in Islamic Education Learning and ethic kindness through method of class seminar. Thpe of research was research of class action executed in two cycles. Every cycle consisted of 4 phase that was planning, executor/action, observation, and reflexion. The data collecting technique was used test, interview, and partisipative observation. In this research, the data technique analysis was used comparative descriptive statistic technique. Pursuant to research result known that average value of student at early condition was 79,70 (under KKM) with the percentage of complete equal to 50,56%. At first cycle the average value of student mount to become 83,91 with the percentage of complete equal to 70,79%. Then at second cycle the average value of student mount again become 91,21 with the percentage of complete equal to 84,27%. Result of these research shows that the students leaning result at Islamic Education Learning and ethic kindness can optimalized through method of class seminar for students of VIII class 1 Public Junior High School of Surakarta odd semester 2015/2016 school year. Therefore, method of class seminar can use as one of the alternative of study method able to be applied by teacher for optimalized learn result at Islamic Education Learning and ethic kindness.